AB0211 Which Disease Activity Score 28 (DAS28) Based Flare Criteria Impact on Functional Disability in Patients with Ra in Das28 Remission State Using The IORRA Cohort. (15th July 2016) - Shidara, K.; Tanaka, E.; Inoue, E.; Yamaguchi, R.; Shimizu, Y.; Hoshi, D.; Sugimoto, N.; Nakajima, A.; Momohara, S.; Taniguchi, A.; Yamanaka, H.
Abstract : Background: The therapeutic goal for patients with rheumatoid arthritis (RA) is achieving remission state or at least low disease activity state. We demonstrated that sustaining remission leads to good functional disability at 1) . However, not a few patients flared after achieving remission state in daily practice. Several published Disease Activity Score 28 (DAS28) based flare criteria are reported 2–5) . It is useful to investigate which DAS28 based flare criteria lead to functional disability. Objectives: To investigate associations between DAS28 based flare criteria and functional disability in RA patients after achieving DAS28 remission in daily practice using the large, observational, Institute Of Rheumatology, Rheumatoid Arthritis (IORRA) cohort. Methods: The IORRA survey has been conducted biannually. RA patients with DAS28 remission in April 2012 (baseline) and participated in both subsequent surveys in October 2012 and October 2013 were extracted from the IORRA cohort. Flare in each patient was evaluated according to four previously published DAS28 based flare criteria [(1) increase in DAS28 >1.2 (2) increase in DAS28 >0.6 or if a DAS28 ≧3.2 (3) reaching DAS28>3.2 (4) reaching DAS28>2.6] 2–5) in October 2012. Functional disability was assessed by validated Japanese version of the Health Assessment Questionnaire (J-HAQ) 6) in April 2012 and October 2013. Change in J-HAQ (ΔJ-HAQ) score was defined as follows: ΔJ-HAQ = J-HAQ score in April 2012 - J-HAQ score in April 2012. Average ΔJ-HAQ score in patients achieving each flare criteria was calculated. The association between ΔJ-HAQ as outcome and achieving each flare criteria as explanatory variable was analyzed using multiple regression analysis adjusting for gender, age, disease duration, pain (Visual Analogue Scale) VAS, general VAS and J-HAQ score at baseline. Results: A total of 1, 874 patients were analyzed. Females comprised 80.6% of the study population. The mean (SD) age and disease duration were 58.2 (12.7) years and 11.9 (8.9) years, respectively. The mean (SD) DAS28 and J-HAQ score were 2.0 (0.5) and 0.3 (0.5), respectively. Proportions of the patients met each flare criteria in October 2012 were (1) 9.7% (2) 24.4% (3) 11.3% and (4) 28.1%, respectively. Average ΔJ-HAQ score in patients met each flare criteria was (1) 0.13, (2) 0.06, (3) 0.10, and (4) 0.05, respectively. Multiple regression analysis demonstrated that achieving each flare criteria significantly associated with increase in J-HAQ score; (1) 0.11 (p<0.001), (2) 0.05 (p=0.0003), (3) 0.10 ((p≤0.001), and (4) 0.04 (p=0.0012), respectively. Conclusions: Regardless of flare criteria, flares resulted in progressed functional disability in patients with RA. Aachieving flare criteria using (1) increase in DAS28 >1.2 and (3) reaching DAS28>3.2 led to worse physical functional outcome, suggesting that usage of these flare criteria might predict functional disability. References: Shidara K et al., the 2011 American College of Rheumatology annual meeting Smolen JS et al., Ann Rheum Dis 2007;66:143–50 VanderCruyssen B et al., Arthritis Res Ther 2010;12:R169 Assous N et al., J Rheumatol 2008;35:31–4 Emery P et al., Ann Rheum Dis 2010;69:1629–35 Matsuda Y et al., Arthritis Rheum 2003;49:784–8 Disclosure of Interest: K. Shidara: None declared, E. Tanaka Speakers bureau: ET has received speaker fees or consulting fees from Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Pfizer, Takeda Pharmaceutical, and Santen Pharmaceutical., E. Inoue: None declared, R. Yamaguchi: None declared, Y. Shimizu: None declared, D. Hoshi: None declared, N. Sugimoto: None declared, A. Nakajima: None declared, S. Momohara Speakers bureau: SM has received speaker fees from Abbott, AbbVie, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Mitsubishi Tanabe, Pfizer, Takeda, and Teijin., A. Taniguchi: None declared, H. Yamanaka Speakers bureau: HY has received speaker fees from Abbott, AbbVie, Asahikasei, Astellas, AstraZeneca, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, GlaxoSmithKline, Janssen, Mitsubishi Tanabe, MSD, Nippon Kayaku, Pfizer, Santen, Taishotoyama, Takeda, and Teijin.